Physical health among the Finnish spinal cord injury population according to the Patient Reported Outcome Measurement Information System (PROMIS®) - Poutanen, Joonas; Anttila, Heidi; Tallqvist, Susanna; Kallinen, Mauri; Koskinen, Eerika; Hämäläinen, Harri; Kauppila, Anna-Maija; Täckman, Anni; Vainionpää, Aki; Arokoski, Jari; Hiekkala, Sinikka (The journal of spinal cord medicine, 2022)
The aim of this study is to assess the physical health in the Finnish Spinal cord injury (SCI) population using the Patient Reported Outcome Measurement Information System (PROMIS®) and make a comparison to the general United States (US) population. Furthermore, the aim is to explore the associations between pain interference, pain intensity, sleep disturbance, and fatigue and physical function. Cross-sectional study. This study is part of the Finnish Spinal Cord Injury (FinSCI) community survey study. Community, Finland. 884 persons with SCI. Not applicable. Physical health was measured with custom Patient Reported Outcome Measure System (PROMIS®) short forms. Higher age and lesion level indicated more severe physical function impairments. Persons ≥46 years exhibited more pain interference symptoms compared to younger participants. On average, the Finnish SCI population had 1.3 SD lower physical function and 0.9 SD higher pain interference T-scores compared to the US general population (P < 0.001). The most significant association was observed between pain interference and physical function (r = −0.364, P < 0.001). The present study provides a description of the state of physical health in the Finnish spinal cord injury population, as well as the associations between the physical health areas. The results highlight the substantiality of pain management in terms of improving physical function. NCT04649814